Effects of exogenous ketone supplementation on blood ketone, glucose, triglyceride, and lipoprotein levels in Sprague–Dawley rats. Issue 1 (December 2016) - Kesl, Shannon; Poff, Angela; Ward, Nathan; Fiorelli, Tina; Ari, Csilla; Van Putten, Ashley; Sherwood, Jacob; Arnold, Patrick; D'Agostino, Dominic
Abstract Background Nutritional ketosis induced by the ketogenic diet (KD) has therapeutic applications for many disease states. We hypothesized that oral administration of exogenous ketone supplements could produce sustained nutritional ketosis (>0.5 mM) without carbohydrate restriction. Methods We tested the effects of 28-day administration of five ketone supplements on blood glucose, ketones, and lipids in male Sprague–Dawley rats. The supplements included: 1, 3-butanediol (BD), a sodium/potassium β-hydroxybutyrate (βHB) mineral salt (BMS), medium chain triglyceride oil (MCT), BMS + MCT 1:1 mixture, and 1, 3 butanediol acetoacetate diester (KE). Rats received a daily 5–10 g/kg dose of their respective ketone supplement via intragastric gavage during treatment. Weekly whole blood samples were taken for analysis of glucose and βHB at baseline and, 0.5, 1, 4, 8, and 12 h post-gavage, or until βHB returned to baseline. At 28 days, triglycerides, total cholesterol and high-density lipoprotein (HDL) were measured. Results Exogenous ketone supplementation caused a rapid and sustained elevation of βHB, reduction of glucose, and little change to lipid biomarkers compared to control animals. Conclusions This study demonstrates the efficacy and tolerability of oral exogenous ketone supplementation in inducing nutritional ketosis independent of dietary restriction.